Obstetric and Perinatal Morbidity in Northern Tasmanian Aboriginal Population: A Retrospective Cohort Study - Rashida Hakeem; Amanda Dennis; Kathryn Ogden; Kiran D.K. Ahuja; Mohammed Abdul Hakeem (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Aboriginal and Torres Strait Islander women are at increased risk of maternal morbidity and mortality as compared to non-Aboriginals. Similarly, aboriginal babies are at increased risk of low birth weight and infant mortality. Aim: To investigate the independent association of aboriginality with Tasmanian maternal and neonatal morbidity. Materials and Methods: A retrospective analysis of all the births (gestation more than 20 weeks) from June 2013 to May 2014 was conducted at the Launceston General Hospital, Tasmania. The study compared 66 Aboriginal (4.2% of the total births) to 1477 non-aboriginal births for maternal and neonatal morbidity. Comparisons were made using logistic regression. The outcome measures were maternal and neonatal morbidity. Results: Significantly higher number of aboriginal women (49% vs 19%; OR 4.15 90%CI 2.52- 6.85) smoked and used illicit drugs (15% vs 2%; OR 9.24; 95%CI 4.28-19.96) than the non-aboriginal women (both p<0.001). Maternal morbidity was not significantly different between aboriginal compared to non-aboriginal women (OR 0.64; 95%CI 0.36-1.14; p=0.13; adjusted OR 1.00; 95%CI 0.52-1.93; p=0.99). Factors positively associated with maternal morbidity included: age (OR 1.28; 95%CI 1.13-1.46; p<0.01) and BMI (OR 1.50; 95%CI 1.33-1.70; p<0.01). The unadjusted OR of neonatal morbidity for aboriginality was 1.98 (95%CI 1.17- 3.34; p=0.01) and adjusted was 1.45 (95%CI 0.77-2.72; p=0.25). Factors positively associated with neonatal morbidity included smoking (OR 2.24; 95%CI 1.59-3.14; p<0.01), illicit drug use 95%CI 1.49-(OR 3.26; 95%CI 1.49-7.13; p <0.01), hypertension (OR 2.49; 95%CI 1.61-3.84; p<0.01) and diabetes (OR 1.92; 95%CI 1.33-2.78; p<0.01). Conclusion: The composite Aboriginal maternal morbidity does not differ, however the increased rates of smoking and illicit drug use are largely responsible for neonatal morbidity. Along with strengthening strategies to decrease medical comorbidities in aboriginals, we recommend intensifying smoking and illicit drug cessation programs.